Domestic violence and childhood trauma among married women using machine learning approach: a cross-sectional study - Abbas Al Mutair; Chandni Saha; Layila Alhassan; Hawra Albahrani; Norah A. Alkhamis; Hajar Al Sultan; Muhammad Daniyal; Alya Elgamri (BMC Public Health)
Abstract Background Globally, 27% of ever-partnered women aged 15–49 have experienced physical, sexual, or intimate partner violence at least once in their lifetime. In Saudi Arabia, domestic violence (DV) remains a concern despite cultural and economic advancements. This study aims to measure the prevalence and factors associated with DV as well as childhood trauma (CT) in the Al Hasa region. Method A cross-sectional study was conducted on 503 married women by using convenient sampling reporting DV and CT using two validated questionnaires, respectively. Descriptive statistics were used to analyze the numbers and percentages. Pearson’s r correlation was applied to investigate the correlation between risk factors. The multilayer perceptron model has been applied to estimate the most important factors contributing to DV and CT. Results Out of 503 respondents, most of them had low experience of DV and childhood trauma, while the prevalence of DV was 4.86%, with controlling behavior of the intimate partner (6.09%) and psychological violence most commonly reported. CT was experienced by 18.90% of respondents, primarily emotional neglect (31.44). The median score of DV was 1.99 (0.81), and that of CT was 2.15(0.45). Among the DV subscales, the median score of psychological violence (2.00, IQR = 0.50) and controlling behavior (2.25 with IQR 0.50) was higher compared to physical and sexual violence, whereas the emotional neglect subscale mean score was the highest among the CT subscales, 2.50 (0.50). DV and childhood trauma were significantly associated with BMI ( $$\:P\:=$$ < 0.001) and education of women ( $$\:P\:=\:$$ < 0.001) respectively. The result of ML model showed that the influential predictors of DV and CT are physical violence and physical neglect respectively. Conclusion The present study revealed a positive correlation between CT and DV. Women who experienced emotional neglect or abuse during childhood were more likely to report controlling behaviors and psychological violence in their relationships. CT was reported more frequently than DV and women with higher education levels reported greater childhood trauma. Even with low prevalence, such sensitive subjects must not be discredited. Saudi women should embrace education, employment, and awareness of their rights with the rapid societal change, marking a new beginning for women’s empowerment and safety.